Nexus between Teacher’s Communication Style and Students’ Academic Performance in Chemistry - Kadiri, Hassan; Na Allah , Mariam Titilayo; Akintola, David Akinjide (EDUCATION JOURNAL OF INDONESIA, 2024)
The study investigated how teacher’s communication styles influence learning outcome in Chemistry. The study adopted a survey research method involving 120 participants randomly selected from secondary schools in South-West Nigeria. Two structured questionnaires were used to collect the data (TRFQS and TRFQT for Chemistry students and teachers respectively). Findings from the study revealed that learners’ academic performance has no direct connection with teacher’s writing and non-verbal style. However, result showed that teacher’s speaking style has influence on learning outcome. The study has implication for school heads, teachers, curriculum planners and learners in their efforts towards enhancing learners’ academic performance.